THE INFLUENCE OF LEADERSHIP STYLE AND GROUP INTEGRATION ON WORK MOTIVATION (Research on Employees at the Gorontalo City-District Office) - Badu, Syamsu Qamar; Djapri , Noviyanty (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This research aims to see the influence of leadership style and group cohesiveness on employee work motivation, with the hypothesis